Localized inhibition of platelets and platelet derived growth factor by a matrix targeted glycan mimetic significantly attenuates liver fibrosis. (February 2021) - Kabra, Harsha; Walimbe, Tanaya; Stuart, Kate; Indey, Camille; Jalgaonkar, Swati; Ikwa, Elvis; Skurnac, Taylor; Chen, Julia; Woolley, Andrew; Snead, Nicholas M.; Bachtell, Nathan; Leeming, Diana J.; et al.
Abstract: New therapeutic strategies are needed for the growing unmet clinical needs in liver disease and fibrosis. Platelet activation and PDGF activity are recognized as important therapeutic targets; however, no therapeutic approach has yet addressed these two upstream drivers of liver fibrosis. We therefore designed a matrix-targeting glycan therapeutic, SBR-294, to inhibit collagen-mediated platelet activation while also inhibiting PDGF activity. Herein we describe the synthesis and characterization of SBR-294 and demonstrate its potential therapeutic benefits in vitro and in vivo . In vitro SBR-294 was found to bind collagen (EC50 = 23 nM), thereby inhibiting platelet-collagen engagement (IC50 = 60 nM). Additionally, SBR-294 was found to bind all PDGF homodimeric isoforms and to inhibit PDGF-BB mediated hepatic stellate cell activation and proliferation. Translating these mechanisms in vivo, SBR-294 reduced fibrosis by up to 54% in the CCl4 mouse model (p = 0.0004), as measured by Sirius red histological analysis. Additional fibrosis measurements were also supportive of the therapeutic benefit in this model. These results support the therapeutic benefit of platelet and PDGF antagonism and warrant further investigation of SBR-294 as a potential treatment for liver fibrosis.